Efforts to Overcome Students' Difficulties in Understanding the Concept of Story Problems with the Problem-Solving Method and the Question and Answer Method in Science Learning - Niel Ananto; Efendi; Baso Intang Sappaile; Cherry Frame Lumingkewas; Ubaidillah (Jurnal Penelitian Pendidikan IPA, 2023)
Science learning concepts are organized logically and systematically from the simplest to the most complex concepts. Students experience difficulties in solving word problems. Word problems have an important role and are often used to assess students' ability to solve problems in questions. The purpose of this study was to determine the effect of the problem solving method and the question and answer method in overcoming students' difficulties in understanding the concept of story questions. The research method uses quantitative methods with one group pretest posttest. The sample in the study was 30 people. The research results obtained that the problem solving method and question and answer method both have a significant value of 0.000 <0.005. So that it can be said that the two methods have a significant influence in efforts to overcome students' difficulties in understanding the concept of word problems.